Critical Pedagogy and the Decolonial Option: Challenges to the Inevitability of Capitalism. (April 2014) - Monzó, Lilia D.; McLaren, Peter
The demise of capitalism was theoretically prophesied by Marx who posited that the world would come to such a state of destruction and human suffering that no amount of coercion or concessions would suffice to stop the massive uprisings that would lead us into a new socialist alternative. Although the downfall of world capitalism may seem ludicrous, we are seeing multiple examples of uprisings across the world and must seize this moment of possibility. Drawing on revolutionary critical pedagogy and decolonial theory, the authors argue that we must look to the subalterns whose geopolitical position of oppression and their experiences with class struggle may provide important models from which we may build future socialist movements. Specifically, the authors discuss briefly some of the successes of the Cuban and Bolivarian revolutions.